Tomato (Solanum Lycopersicum) Growth and Production Response On the Provision of Goat Manure and Trichoderma - Umi Isnatin; Parwi, Parwi; Etica, Use; Bintaro, Rudi (ITScience (Information Technology and Science), 2025)
Chemical fertilizers are commonly used a lot in tomato (Solanum lycopersicum) farming to speed up development and make more fruit. This research looks at how goat dung and the biological agent Trichoderma affect the growth and productivity of tomato plants in an attempt to find more environmentally friendly options. The experiment used a fully randomized factorial design (CRD) with three replications. It tested three levels of goat dung (0, 10, and 20 tons/ha) and three levels of Trichoderma treatment (0, 5, and 10 g/g/ g/plant). The results showed that there was no substantial interaction between the manure and Trichoderma treatments, although each element had an effect on several plant metrics on its own. The 20 tons/ha dosage of goat dung had the most impact on the number of leaves, the weight of the fruit, and the amount of organic carbon in the soil. Trichoderma made a big difference in the number of branches and the weight of the fruit. The most significant changes were seen at 10 g/g/ g/plant. These results show that adding organic matter and living things to tomato plants may help make them healthier and more productive. Using 20 tonnes of goat manure per hectare or 10 grams of Trichoderma per plant is a potential eco-friendly way to minimize reliance on chemical fertilizers while maintaining or even increasing crop output and soil fertility. This study backs the idea of using environmentally friendly farming methods for growing tomatoes.